Country profile: sport and physical activity policy in Scotland - Meir, D.; Brown, A.; Macrae, E.; McGillivray, D. (International Journal of Sport Policy and Politics, 2023)
As a result of the successful devolution referendum in 1997 and the passing of the Scotland Act 1998, several legislative powers were devolved from the Government of the United Kingdom to the new Scottish Parliament including responsibility for sport, health and education. In consideration of this initial constitutional change, and subsequent amendments to taxation and welfare, this country profile provides an overview of how sport is organised and governed in Scotland, including the evolving trends in sport and physical activity policy. The aim is to analyse sport and physical activity policy in Scotland and to explore the wider social, political and economic challenges that impact upon its successful enactment. The profile begins with a historical evaluation of sport in Scotland and the key policy developments that have shaped it across the 20th and 21st century. This is followed by an evaluation of the current politics, structure and funding of sport in Scotland. In building upon those evaluations, three significant and inter-connected contemporary issues in Scottish sport are critically analysed. Whilst there are other relevant contemporary issues worthy of critique, we contend that (1) mega sport event legacies; (2) equality and inequality in sports participation and, (3) health inequalities are the most relevant to the Scottish Governments wider policy agenda and the role of sport and physical activity within it. Finally, a summary of the key findings is presented alongside recommendations for future research in sport and physical activity in Scotland.